BS ISO 9924-1. Rubber and rubber products. Determination of the composition of vulcanizates and uncured compounds by thermogravimetry. Part 1. Butadiene, ethylene-propylene copolymer and terpolymer, isobutene-isoprene, isoprene and styrene-butadiene rubbers (10th August 2022) - British Standards Institution,
No abstract available